TEST ANXIETY AND ACADEMIC ACHIEVEMENT: EXPLORING THE CONNECTION AMONG SECONDARY SCHOOL STUDENTS - Gopalakrishnan, Anisha V.; Baby, Jisha; Francis, Shaiju; Jose, Dr. Sunitha Susan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The major aim of this research study is to explore the relationship between test anxiety and academic achievement of secondary school students. A sample of 350 students was randomly selected from different schools from Kottayam district. Data were collected by using the Test Anxiety Scale (TAS) developed by the investigators. It was found there is a negligible positive correlation between Test anxiety and Academic Achievement of secondary school students. Though the relationship is positive, any increase or decrease in the scores of Academic achievements will be followed by the increase or decrease in the Test anxiety.